Futuristic trends for sustainable development and sustainable ecosystems - Quintero, Jose Melchor Medina; Iyer, Sailesh; Tiwari, Sanju; Ortiz-Rodriguez, Fernando (IGI Global, 2022)
"This book communicates the recent advances in ICT (Information Communications and Technology) by covering practices in several artificial intelligence (AI) fields, such as knowledge representation and reasoning, natural language processing, machine learning, and the semantic web.
Includes bibliographical references and index. - Mode of access: World Wide Web
Keywords: Environmental protection -- Data processing; Sustainable development -- Data processing; Artificial intelligence -- Industrial applications